Genetic diversity analysis for seed yield and quality characters in sesame (Sesamum indicum L.): GENETIC DIVERSITY ANALYSIS IN SESAME - S R KUMHAR; B R CHOUDHARY; S PAROHA (Journal of Oilseeds Research, 2013)
Genetic divergence wasstudied by growing thirty six genotypes ofsesame, Sesamum indicum L. at Agricultural Research Station, Mandor, Jodhpur during rainy season 2010. The mean sum of squares were significant for all the characters, indicating the presence of variability. Characters like seed yield, free fatty acid, oxalic acid content, number of productive capsules/plant and productive branches/plant exhibited high heritability coupled with high genetic advance revealing that these characters were controlled by additive gene action. The hierarchical cluster analysis indicated the presence of considerable genetic divergence among the genotypes. The genotypes were grouped into seven clusters using Ward’s minimum variance method. The intercluster Euclidean2 distance was maximum between cluster III and VII (42.71) followed by cluster VI and VII (41.90) and cluster II and VII (39.03) which indicated that the genotypes included in these clusters will give high heterotic response and thus better segregants. The maximum cluster means were revealed by cluster III for days to 50% flowering, maturity, number of productive branches/plant, oxalic acid content and free fatty acid followed by cluster VI for seed yield, number of productive capsules/plant and oil content, and clusterI and IV for plant height and 1000 seed weight,respectively. While cluster VII showed minimum cluster mean for days to maturity, plant height and free fatty acid and cluster I and IV for oxalic acid and days to 50% flowering. Among the 10 characters, number of primary branches/plant contributed the most (12.06%) towards the divergence of genotypes.